Handbook of machining and metalworking calculations - Walsh, Ronald A. (McGraw-Hill's AccessEngineering., 2001)
ESSENTIAL MACHINING AND METALWORKING CALCULATIONS IN THE PALM OF YOUR HAND Solve virtually any problem involving metalworking and machining tools and applications -- quickly and easily with the help of one convenient hands-on resource ready-made for your benchtop or workstation . It"s Ronald A. Walsh"s Handbook of Machining and Metalworking Calculations, and it puts design, operations, repair, and maintenance answers right where you want them--close at hand. You get: Basic to advanced calculation procedures Latest ANSI and ISO specifications Examples of solved problems Calculations for gears, sprockets, springs, screws, threads, ratchets, cams, linkages, notches, flanges, holes, broaching, boring, reaming, turning, pitch, torsion, tension, and more Fit classes and their calculations Easy-to-use tables, charts, listings, and formulas.